Enhanced Rainfall‐Induced Shallow Landslide Activity Following Seismic Disturbance—From Triggering to Healing. Issue 1 (9th January 2021) - Leshchinsky, Ben; Lehmann, Peter; Or, Dani
Abstract: Evidence suggests that following earthquakes, landslide activity, and susceptibility remain elevated for months to years after cessation of shaking. In landslides constrained within the soil mantle, enhanced post‐seismic activity may be attributed to persistence of progressive failure surface development that results in delayed triggering. With subsequent post‐seismic hydrologic disturbance, a commensurate decay in activity over time reflects evacuation of damaged hillslope materials and mechanical healing of colluvial media and vegetation recovery. In this study, we propose a hydromechanical model for representing the interplay of these processes including trends in timing and magnitude of post‐seismic shallow landslide activity. The hydromechanical model considers seismic or hydrologic disturbances as drivers for failure surface development in the soil mantle over a hillslope with commensurate weakening through accumulation of internal compression, shear softening, and loss of root strength. In the absence of well‐instrumented post‐seismic landslide measurement of evolving stress conditions and deformation, predictions were made against a unique field case study where hydrologically induced hillslope failure kinematics and internal compression were measured. The model accounts for seismic disturbances, demonstrating that certain peak ground accelerations directly reduce subsequent rainfall‐induced landslide‐triggering thresholds relative to undisturbed hillslopes. The model framework can be used to describe progressive, post‐seismic landslide activity, demonstrating that consideration of root or soil healing may suppress subsequent landslide triggering and contribute toward recovery to pre‐seismic disturbance levels of strength. Factors such as shear softening, vegetation, and healing are explored in the context of the temporal evolution of landslide rates after a seismic event. The results of this paper show mechanistically how (1) progressive development or cessation of a failure surface in active, post‐seismic landslides may describe elevated post‐seismic landslide rates and (2) that hillslope healing plays a modest role in the magnitude and timescale of attenuated landslide activity.